100 Making decisions and sharing information, the patient experience: the UK Multiple Sclerosis Register (UKMSR). Issue 6 (27th May 2022) - Ramsay, Stephen; Magill, Fiona; Goldsmith, Grainne; Kee, Rachael; McKee, Jon; Middleton, Rod; Nicholas, Richard; Kennedy, Fiona; Hughes, Stella; McDonnell, Gavin
Abstract : Objective: To evaluate the exchange of information and communication between MS patients and the clinical team regarding decisions around disease modifying therapy (DMT) and MRI results utilising the UKMSR, an established, validated cohort of people with MS. Methods: An online questionnaire was designed and then disseminated to patients in February 2020. Results: From 2512 responses, 44% were on DMT (86% had RRMS). Of 1089 responses, 60% indicated that the decision to start DMT was made with the clinical team, whilst 13% responded it was "largely my teams' decision". Only 117 (~10%) felt they received "too little information". Overall, 2459 patients had undergone ≥1 MRI, with 70% seeing the images at least once. Almost 90% of patients would be interested in viewing scans at clinic, appearing independent of DMT exposure, although 2/3 of those who were "not interested" were not on DMT. Conclusions: A majority of study participants reported adequate involvement and sharing of information in the decision-making process when starting DMT although a concerning minority appear disengaged. Patients are very interested in viewing MRI scans with a majority having had this opportunity. Not all expressed such an interest however. Patient preference should therefore be duly considered in clinical management. sramsay03@qub.ac.uk|ABN Bursary